Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai di Dinas Pendidikan Dan Kebudayaan Kota Bukittinggi - Fadilul Rahman; Irsyad Irsyad; Merika Setiawati; Tia Ayu Ningrum (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Employee performance is an important factor in supporting the effectiveness of public sector organizations, including regional education institutions. One factor that is assumed to influence employee performance is leadership style. This study aimed to determine and analyze the effect of leadership style on employee performance at the Department of Education and Culture of Bukittinggi City. The study employed a quantitative approach with a causal associative design. The population consisted of 72 employees, with 61 respondents selected using the Proportional Random Sampling technique. Data were collected through questionnaires using a Likert scale, while data analysis was conducted using descriptive analysis, prerequisite tests, and simple linear regression with the assistance of SPSS version 26. The results indicated that leadership style had a positive and significant effect on employee performance, with a significance value of 0.004 < 0.05. The leadership style variable obtained a Respondent Achievement Level score of 81.80% and was categorized as good, while employee performance obtained a score of 85.20% and was also categorized as good. The coefficient of determination showed that leadership style contributed 13.2% to employee performance, while the remaining 86.8% was influenced by other factors outside this study. The novelty of this study lies in the use of the behavioral approach in examining leadership style within the context of regional educational organizations.